Synthesis, in silico studies and in vitro cytotoxicity evaluation of novel posaconazole derivative as a ALK TK inhibitor - Rahul D. Jawarkar; Praveen Sharma; Sachin Jain; Umang Shah; Magdi EA Zaki; Sami A Al-Hussain; Suraj Mali; Chin-Hung Lai; Vijay H. Masand; Vivek T Humne (Journal of Taibah University for Science)
Oncology research progresses, yet cancer remains the largest medical need. The use of a medication with an accessible lead molecule shows great potential for long-term cancer therapy. It may help target cancer therapy and drug resistance. This work uses FDA-approved, clinically proven compounds to build novel cancer therapeutic ligands to prevent treatment resistance. Based on the reported findings, an in-silico docking experiment was performed using FDA-licensed fungus medication posaconazole. The ALK TK pdb:4cmu ligand and posaconazole docked similarly in the research. Posaconazole's in silico docking findings were then tested against A549 lung cancer cells. Posaconazole, the lead, underwent an ADME investigation. Given in silico and experimental confirmation, acetyl, benzyl, and benzoyl derivatives of the lead molecule posaconazole was synthesized. IR, mass, 1H NMR, 13C NMR, and elemental analysis were performed on the synthesized compounds. Next, the three variants were evaluated against A549 lung cancer cells. They were then examined by utilizing computational approaches such as molecular docking, DFT analysis, MD simulation, and MMGBSA analysis. The ADME studies were conducted on posaconazole and its derivatives based on the in-vitro cell line investigation. Based on the results of an ADME study, two new ALK TK inhibitors that don't work as Pgp substrates are good lead candidates. Thus, the present investigation fruitfully reported two lead drug candidates against the issue of resistance in cancer therapy.